2016
DOI: 10.1142/s2424835516500260
|View full text |Cite
|
Sign up to set email alerts
|

A Classification for Extensor Carpi Ulnaris Groove Morphology as an Aid for Ulnar Sided Wrist Pain

Abstract: Our classification system of ECU groove morphology will help identify different components to ulnar sided wrist problems and may help establish guidelines for treatment. This classification system has been validated for both cadaveric specimens and the MRI scans. It showed substantial agreement to almost perfect agreement in the data tested, thus proving good interand intra-observer reliability. It is a useful tool to help in further research into ulnar sided wrist pain and ECU instability, and may help develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Singh et al, in their cadaver study, classified the distal ulna groove according to the C, L and S types ; they reported that the S type is shallower, and the L type is flatter. With MR evaluation in cadavers, dislocation rates of 8% for C type, 33% in L type and 47% in S type, were shown (28).…”
Section: Discussionmentioning
confidence: 97%
“…Singh et al, in their cadaver study, classified the distal ulna groove according to the C, L and S types ; they reported that the S type is shallower, and the L type is flatter. With MR evaluation in cadavers, dislocation rates of 8% for C type, 33% in L type and 47% in S type, were shown (28).…”
Section: Discussionmentioning
confidence: 97%
“…Despite the increased amount of available information about ECU instabilities, there are new records [12][13][14] in the literature describing anatomical variations which are not involved in classification schemes [8][9][10]. Hand surgeons have to cope with these "anomalies and variations" during surgical operations.…”
Section: Eine Neue Umfassende Klassifikation Für Ecu-sehnenprobleme A...mentioning
confidence: 99%
“…Since the time of the most recently-published classification, many articles have been published providing descriptions of ulnar anatomy variations [12,13]. ECU tendon instability was also recorded in healthy individuals.…”
Section: New Biomechanical and Anatomical Knowledgementioning
confidence: 99%
See 1 more Smart Citation